Balancing Green: When to Embrace Sustainability in a Business (and When Not To) - Sheffi, Yosef (Cambridge, MA : The MIT Press, 2018)
"As Yossi Sheffi began researching this book, he and his team noticed a gap: not only between companies that pay lip service to the idea of sustainability but do not change their practices, but also between consumers who say that sustainability is important to them but are unwilling to pay more for sustainable products. How is a company supposed to embrace sustainability and environmental stewardship in this climate? Sheffi argues that there are three main reasons for corporate sustainability efforts, and none of them have to do with the actual environment. Pursuing sustainability can help cut costs, reduce risk, and grow a company. These values make sustainability worth pursuing regardless of one's beliefs about climate change and eliminate the false choice between the environment and the economy. This book is built on extensive interviews with executives at leading companies, as well as significant secondary research about what executives, activists, governments, and academics have to say about corporate sustainability. It is rich with examples of sustainability efforts from companies like Nike, Starbucks, and IKEA, and features extended case studies of Dr. Bronner's Magical Soaps, Patagonia, and Seventh Generation"-
Keywords: Business logistics -- Environmental aspects; Sustainability; Social responsibility of business; Environmental economics